The factors on metallic iron crystallization from slag of direct coal liquefaction residue SiO2-Al2O3-Fe2O3-CaO-MgO-TiO2-Na2O-K2O system in the entrained flow gasification condition. (15th June 2019) - Li, Xiaoming; Zhi, Lifei; He, Chong; Kong, Lingxue; Bai, Jin; Guhl, Stefan; Meyer, Bernd; Li, Wen
Highlights: The metallic iron reduced by atmosphere occurs only in pulverized coal gasifier. The metallic iron is inhibited by increasing SiO2 /Al2 O3 or decreasing Fe2 O3 or CaO. The Si 4+ of the liquid slag relates closely with the iron crystallization. Sand, or mullite, or coal blending is required to inhibit metallic iron. Abstract: The gasification of direct coal liquefaction residue (DCLR) enhances the overall economy of the direct coal liquefaction process. However, the DCLR ash is rich in iron due to pyrite as the catalyst during liquefaction. Coal blending plan with DCLR for gasification should consider the possibility of metallic iron crystallization and agglomeration ahead of suitable viscosity range. In this study, the iron behavior in the DCLR slag in the gasification condition was discussed by the thermodynamic modelling of SiO2 -Al2 O3 -Fe2 O3 -CaO-MgO-TiO2 -Na2 O-K2 O. Results show that the metallic iron forms only in the dry feed entrained flow gasifier for the high content of reducing gases. The metallic iron crystallizes when Fe 2+ of the liquid phase fails to be stabilized by -Si-O. The competition reaction with -Si-O between Ca 2+ and Fe 2+ and the formation of calcium aluminum-silicate also contribute the metallic iron crystallization. In the gasification condition, the metallic iron crystallization can be inhibited by decreasing the iron content/α value (α = CaO/(SiO2 + Al2 O3 ), mass ratio) or by increasing S/A (S/A = SiO2 /Al2 O3, mass ratio) of DCLR ash. Finally, the DCLR blends with 3.5 wt% sand/8.0 wt% mullite/50.0 wt% Dalai Nur coal/90.0 wt% Duolun coal is the feasible feedstock for pulverized coal gasifier, because the temperature of iron crystallization is below the tapping temperature of 1350 °C and the viscosity is less than 25 Pa·s.